Evaluation of the Bio Protective Value of the Leaves of Sixty Varieties of Taro (Colocasia Esculenta) Cultivated in Burkina Faso - Amana, METUOR DABIRE; Helene, OUOBA Boampoundi; Samson, GUENNE; Veronique, ZONGO Sidnooma; Hemayoro, SAMA; Ernest, TRAORE Renan (Journal of Asian Scientific Research, 2022)
Colocasia esculenta is a plant of the family of Araceae, of Asian origin, known under the name of taro. Taro is a perennial herbaceous plant whose large leaves are mainly used human consumption in several countries. It is grown in Burkina Faso mainly for its tubers. However, taro leaves are eaten sparingly in Burkina unlike other countries which have made it a staple food. Furthermore, we know that edible leaves are nutrient-rich and bio-protective in nature. The objective of this work was to determine the composition of bioactive elements in these leaves in order to detect their bioprotective role. Analysis of the bioactive constituents gave the following results: flavonoids (3.08 to 270.55 µg EQ / 100 mg fresh leaves), total phenols (46.06 to 474.02 µg Gallic Acid Equivalent (GAE) / 100 mg fresh leaves), acid ascorbic (3.37 to 154.69 µg / 100 mg fresh leaves), 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) (5.26 to 52.21 µg Ascorbic Acid Equivalent (AAE) / 100 mg fresh leaves), Ferric Reducting Assay Power (FRAP) (181.39 to 886.77 µg AAE / 100 mg leaves fresh). This study allowed us to conclude that taro leaves (Colocasia esculenta) studied were of protective interest with regard to their compositions as secondary food metabolites.